OVERVIEW OF KNOWLEDGE AND ATTITUDES OF ADOLESCENT WOMEN REGARDING VUCILITY IN SMAN 3 KOTA BAUBAU - Ribay, Asmiran; Salim, Ika Lestari; Lestari, Wa Ode Sriwati (Institut Kesehatan dan Teknologi Buton Raya, 2024)
Vaginal discharge is when discharge other than blood from the vaginal canal is out of the ordinary, either odorless or odorless and accompanied by itching. Vaginal discharge is one of the reproductive health problems for teenagers, especially women, which is often complained about and is currently an inconvenience in carrying out daily activities. To find out knowledge and attitudes of young women about vaginal discharge or at SMAN 3 Baubau City in 2023. This research uses a narrative descriptive research type, research subjects are young women in class and preparation of results and discussion. Knowledge analysis showed that 35 respondents (68.4%) had a good level of knowledge. and the attitudes of 41 respondents (80.4%), where class XI female students have good knowledge but their attitudes are still lacking, especially personal hygiene at SMAN 3 Baubau in 2023.